(untitled) (Fiep Bulletin - online, 2025)
Currently, antigens are known as foreign bodies, invaders, and even threats to our organism that require antibodies to eliminate them. There is, therefore, a need for greater scientific clarification about the multiple ways in which our genetic inheritance is articulated and how the molecules in our body interact, potentially transforming into various types of genetic inheritance that form specific labels and QR codes that follow and respect a cellular criterion imposed by Guanines in the four established genetic inheritances. These molecules, particularly antigens, are reading strands with extraordinary capabilities; they perform commands, cleavages, executions, connections, fittings, and transports, create new molecules, and carry out any additional events the organism needs. For example, we have the concept of a high-level encoding, where several names for these events are mentioned in the Bible. This encoding reaches the cell through a specific trio of microtubules. Antigens exert control over B lymphocytes, T lymphocytes, antibodies, and immune system defense groups, conducting cellular surveillance and activating these groups within the immune system. In genetics, they are of extreme importance, commanding rapid reading strands such as RNAs and Uracil, and constructing large, extra-specific encoding strands. In the blood, they are responsible for forming Agape Bi G Blood, the famous "Golden Blood" or "Null Blood," exclusive to higher-level and extra codifications. They control three systems: immune, genetics, and blood.